THE ESTIMATION OF THE CIRCLED FORM OF PERFORMANCE INFLUENCE ON THE DEVELOPMENT OF THE SPEED IN THE PHYSICAL EDUCATION TEACHING - Drago Milošević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
On the sample of 108 students from the 1st and 2nd secondary school classrooms in Kolashin, which is divided for this research into two subsamples ( 54 of the tested students make experimental and 54 tested students make control group ), was applied the circled form of performance, in the basic part of the lesson for the experimental group, in order to establish the level of contribution of this type of the teaching method on the development of the speed. The control group had made by the teaching program the determined instruction of physical education. The initial and the final measurements of the tests were made. For estimation of the latent speed ability for both subsamples 6 tests were applied. The influence of the circled work method on the development of the examined mobility ability, in the experiment lasted 4 teaching months, was established by the discriminative analyses. The obtained coefficients of the discriminative analyses have shown that the tested students from the experimental group, in the statistical sense, importantly improved their speed level at the final than at the initial measurement. The experiment also showed that the obtained results on the final measurement, in the statistical sense, are much bigger within the experimental than within the control group.